Novel insight into the gel phase of Hevea natural rubber - Ehabe, E.E. (2023)
In a suitable organic solvent, Hevea natural rubber (NR) disintegrates into an insoluble gel phase (macrogel) and a sol phase consisting of polyisoprene chains with micro-aggregates (microgel). Studies on Hevea microgel following the advent of its quantitation by steric exclusion chromatography (SEC) are quite recent. In this study, transesterification of NR favoured macrogel elimination with unclear effects on the microgel. The NR’s structure and the relative gel quantities varied in solution (depending on the solvents used) and during transesterification to produce substantial quantities of low-to-average molar mass chains (probably from the macrogel and/or the microgel fraction). The macrogel broke down equally to microgel. This microgel, representing 25%–30% Hevea rubber, remained insensitive to transesterification. The NR’s structure was made up essentially of variably-sized membrane-delimited entities. On dissolution, these entities were denatured and through this liberated more or less branched polyisoprene chains, as well as some microgel and macrogel.